KOMITMEN ORGANISASI, LOCUS OF CONTROL, DAN KOMPLEKSITAS TUGAS TERHADAP KINERJA AUDIT INTERNAL - Khikmah, Siti Noor; Priyanto, Edi (Jurnal Analisis Bisnis Ekonomi, 2009)
This research aim to: (1) to knowing organizational influence komitmen to internal auditor performance at office BAWASDA in Karisidenan Kedu. (2) knowing influence of locus of control to internal auditor performance at office BAWASDA in Karisidenan Kedu. (3) knowing influence of duty complexity make an audit of to internal auditor performance at office BAWASDA in Karisidenan Kedu. (3) knowing influence of duty complexity make an audit of to internal auditor performance [at] office BAWASDA in Karisidenan Kedu. (4) knowing organizational influence komitmen, locus of control, and duty complexity make an audit of to internal auditor performance at office BAWASDA in Karisidenan Kedu. this Research population is entire laboring responder as internal auditor ( Functional Functionary of Auditor) at office BAWASDA in Karisidenan Kedu, with the amount 110 internal auditor. Sampel used in this research 79 internal auditor or Functional Functionary of Auditor in 4 office BAWASDA. technique of sampel by convinance sample. Data collecting use the kuesioner. Test the validity use the technique of product moment, and test the reliabilitas use the Alpha Cronbach>0.60. this Hipotesisi Research use the doubled linear analysis regresi. doubled Linear result of organizational komitmen, locus of control, and duty complexity make an audit of by together have an effect on the signifikan to internal auditor performance by R Square of equal to 55,5%.